2018
DOI: 10.1002/pen.25008
|View full text |Cite
|
Sign up to set email alerts
|

Acoustically and thermally insulating epoxy foams prepared by non‐traditional expandable microspheres

Abstract: Herein, the acoustically and thermally insulating epoxy foams were prepared using non‐traditional expandable microspheres. The effect of foaming temperature and microsphere content on the morphology, the mechanical strength, the thermal insulation and acoustical properties of the epoxy foams was investigated in detail. It can be found that the closed pores can be partially opened by adjusting the preparation parameters, which is also accompanied by obvious changes in acoustic and thermal insulation properties.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 36 publications
(42 reference statements)
0
17
1
Order By: Relevance
“…Foams within the same density set present fairly similar cell morphology and cell size distribution (Figure 4), with average cell size and wall thickness ranging from 125 ± 5 µm and about 1–2 µm to 56 ± 2 µm and 10–12 µm for low- and high-density foams, respectively (Table 2). The cellular morphology of previous studies presents either a bimodal cell size distribution or the presence of extremely large cells [5,18,20,21,22,23], neither of these two effects were observed in our samples (Figure 4). We ascribe this homogeneity of the cellular structure to the single-step foaming process and to the degassing of the CNP mixture.…”
Section: Resultscontrasting
confidence: 54%
See 2 more Smart Citations
“…Foams within the same density set present fairly similar cell morphology and cell size distribution (Figure 4), with average cell size and wall thickness ranging from 125 ± 5 µm and about 1–2 µm to 56 ± 2 µm and 10–12 µm for low- and high-density foams, respectively (Table 2). The cellular morphology of previous studies presents either a bimodal cell size distribution or the presence of extremely large cells [5,18,20,21,22,23], neither of these two effects were observed in our samples (Figure 4). We ascribe this homogeneity of the cellular structure to the single-step foaming process and to the degassing of the CNP mixture.…”
Section: Resultscontrasting
confidence: 54%
“…Several studies by Bao and coworkers [18,19,20,21,22,23] on epoxy/Expancel systems reported two-step foaming processes, composed of pre-curing at low temperatures (around 45 °C) and foaming (75 to 100 °C temperature range), followed by traditional epoxy post-curing. The authors stated their intention to adopt a single-step process but they encountered thermal degradation of the matrix.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their expansion is easily controllable and irreversible due to the plastic deformation of the polymer shell (see Figure S1b), which makes it an ideal candidate for simple preparation of tunable surface microstructures. Although TEMs have been widely used for stimuli-response composites and thermally insulating materials, their application for active sensing materials has not yet been exploited. These unique characteristics of graphene and TEMs combined with silicone rubber encouraged us to develop a mold-free, low-cost, and feasible approach to realize thermally regulated surface microstructures for high-performance microstructured pressure sensors.…”
Section: Introductionmentioning
confidence: 99%
“…At a certain high temperature, the alkane inside the TEMs, as core material, could be gasified, thereby generating pressure to expand the softened copolymer shell, finally realizing an increase in the volume of the microspheres as several times larger than their initial state. Based on this unique property, TEMs gradually permeates a number of fields and products, such as adhesives, 1,2 foamed plastics, 3,4 three-dimensional coatings, 5 and even vehicle manufacturing industries. 6 Nevertheless, owing to the increasingly enhanced environmental awareness throughout the world, renewable and degradable biological materials receive much attention.…”
Section: Introductionmentioning
confidence: 99%